Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006425
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal breastfeeding education for increasing breastfeeding duration

Abstract: Background-Breastfeeding (BF) is well recognised as the best food for infants. The impact of antenatal BF education on the duration of BF has not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
2
1
2
Order By: Relevance
“…Thus, the effectiveness observed in this review by peer counseling (via telephone) on breastfeeding differs from the results found in other studies or reviews in the literature, in which peer counseling (when well delineated) has been configured as a source of support and encouragement for puerperal women, obtaining good results in relation to the duration and exclusiveness of BF (36)(37) .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Thus, the effectiveness observed in this review by peer counseling (via telephone) on breastfeeding differs from the results found in other studies or reviews in the literature, in which peer counseling (when well delineated) has been configured as a source of support and encouragement for puerperal women, obtaining good results in relation to the duration and exclusiveness of BF (36)(37) .…”
Section: Discussioncontrasting
confidence: 82%
“…Peer counseling was used in the educational intervention in three of the analyzed clinical trials. Peer counseling is a form of intervention that has been consolidated in international studies, and which consists of people who have had positive experiences with certain situations promoting support and counseling for their peers (36)(37) . Although the peers were trained by health professionals to provide telephone support for women who were breastfeeding, two studies investigated in this review that used peer counseling over the telephone found no significant efficacy in the duration or exclusiveness of BF (27,29,33) .…”
Section: Discussionmentioning
confidence: 99%
“…Los instrumentos empleados para el análisis crítico de la evidencia recuperada fueron: el AGREE para Guías de Prácticas Clínicas, que evalúa tanto la calidad de la información aportada en el documento como la calidad de algunos aspectos de las recomendaciones (Coello, 2004) y el CASPe, un programa para ayudar a adquirir habilidades en el análisis y en lectura crítica de la literatura científica en salud (Lumbiganon, et al, 2011) RESULTADOS Los resultados obtenidos de los 12 documentos encontrados son producto de la aplicación de las plantillas CASPe según el tipo de investigación y AGREE para el caso de guías de práctica clínica. Estos se despliegan a continuación: informan que, existe evidencia que señala que la discusión en clases prenatales informales y con pocos participantes, lideradas por profesionales de la salud que enfaticen en los beneficios de la lactancia y den consejos prácticos, pueden aumentar las tasas de inicio de lactancia materna.…”
Section: Materiales Y Métodosunclassified
“…Además, las intervenciones que combinan la educación sanitaria antes del nacimiento, junto con apoyo durante los días inmediatamente posteriores a este, deben evaluarse y compararse con aquellas que solo ofrecen educación. Lumbiganon, et al (2011), después de efectuar una revisión sistemática de artículos, concluyen que "hay una necesidad urgente de realizar un estudio controlado aleatorio de alta calidad, con un tamaño de muestra adecuado y que esté exento de influencias comerciales para evaluar la efectividad de la educación en lactancia materna." (p.10).…”
Section: Materiales Y Métodosunclassified
“…Breastfeeding education is a process within a program that aims to provide information, shape attitudes, and instill correct behaviors for a speci c purpose and target audience. It can occur individually, in group settings, through clinical training, home visits, and peer education programs [11][12][13] . With the advancement of technology, web-based education, as well as traditional education, is widely used in many elds.…”
Section: Introductionmentioning
confidence: 99%